Impact of Gender and Age in HbA1c Levels among Libyan Adults Without Known Diabetes in Zeletin City, Libya: A Cross-Sectional Study - Zaidi, Aisha; Wafa Elmghirbi; Warida El-Rwegi; Ahmed Algdar; Huda Saleh (AlQalam Journal of Medical and Applied Sciences, 2024)
The objective of our study was to examine the correlation between HbA1c levels, gender and age in Libyan adults in Zeletin city who have not been diagnosed with diabetes. In our cross-sectional study, we enrolled a total of 300 participants. Blood samples were collected from each participant and subsequently analyzed to determine their HbA1c levels. Statistical analysis included t-tests, linear regression analysis, and one-way ANOVA. Our results showed a significant positive correlation between HbA1c levels in relation to both age and gender. Furthermore, approximately 58.7% of the individuals had HbA1c levels equal to or exceeding 6.5%, which is commonly used as a threshold for diagnosing diabetes. This indicates that there is a notable occurrence of undiagnosed diabetes within the participants of the study. When examining different age groups, we observed a substantial increase in HbA1c levels with advancing age. Additionally, in the 50-59 and above 60 age groups, males exhibited significantly higher HbA1c levels compared to females (p<0.001). In conclusion, our study validated the previously observed link between elevated HbA1c levels and increasing age in individuals without diabetes. Additionally, our study highlights a high prevalence of undiagnosed diabetes in Zeletin, Libya, suggesting an impending increase in diabetes cases that will pose a significant economic burden on healthcare. كان الهدف من دراستنا هو فحص العلاقة بين مستويات السكري التراكمي والجنس والعمر لدى البالغين الليبيين في مدينة زليتن الذين لم يتم تشخيص إصابتهم بمرض السكري. في دراستنا المقطعية، قمنا بتسجيل ما مجموعه 300 مشارك. تم جمع عينات الدم من كل مشارك وتحليلها لاحقًا لتحديد مستويات السكري التراكمي لديهم. وتضمن التحليل الإحصائي اختبارات تحليل الانحدار الخطي، وتحليل التباين الاحادي. أظهرت نتائجنا وجود علاقة إيجابية كبيرة بين مستويات السكري التراكمي فيما يتعلق بكل من العمر والجنس. علاوة على ذلك، كان لدى ما يقرب من 58.7% من الأفراد مستويات السكري التراكمي تساوي أو تتجاوز 6.5%، والتي تستخدم عادةً كعتبة لتشخيص مرض السكري. يشير هذا إلى وجود نسبة ملحوظة لمرض السكري غير المشخص بين المشاركين في الدراسة. عند فحص الفئات العمرية المختلفة، لاحظنا زيادة كبيرة في مستويات السكري التراكمي مع تقدم العمر. بالإضافة إلى ذلك، في الفئات العمرية 50-59 وما فوق 60 عامًا، أظهر الذكور مستويات السكري التراكمي أعلى بكثير مقارنة بالإناث. في الختام، أثبتت دراستنا العلاقة التي تمت ملاحظتها سابقًا بين مستويات السكري التراكمي المرتفعة وزيادة العمر لدى الأفراد غير المصابين بالسكري. بالإضافة إلى ذلك، تسلط دراستنا الضوء على ارتفاع معدل انتشار مرض السكري غير المشخص في زليتن، ليبيا، مما يشير إلى زيادة وشيكة في حالات مرض السكري من شأنها أن تشكل عبئا اقتصاديا كبيرا على الرعاية الصحية